Menu do dia: a influência da adição do atributo orgânico na intenção de compra de alimentos in natura e processados - Silva, Francielih Dorneles (2016)
The demand for organic food has grown and due to this fact, many researchers have been trying to understand the motivations that lead consumers to buy these foods. Some researches related to the behavior of these consumers have shown that they consider organic food healthier and ecologically than traditional food. In this context, many organizations, such as retailers or restaurants, have suited themselves to provide products and promote experiences to the consumers that include sustainable and healthy offers. Considering these aspects, the main goal of this research was to analyze the influence on buying intention, when the “organic” attribute is added to in natura and processed food. Thus, the contributions of this study, that also justify it, dwell in: i) the lack of researches related to consumer´s behavior regarding organic food, in Brasil, especially when this type of food is processed, once the majority of studies found in academic literature are related to in natura food; ii) understanding the impact of the organic attribute on consumer’s decision, in different contexts of consumption; iii) the managerial and social contributions resulted from the analysis of organic food consumers’ behavior; iv) the use of experimental method, once its usage is relatively recent in this area and it is considered suited to explain the movement of marketing phenomena. Thus, three quantitative, experimental studies were developed and analyzed through statistical techniques, namely: t test for analysis of differences between two groups, ANOVA for differences between more than two groups, chi-square to compare frequencies observed in categories of different samples and linear regression used with the purpose of predicting a single dependent variable from the knowledge of an independent variable. The first study highlighted the “organic” attribute in restaurants’ menus and 501 surveys questionnaires were collected. As a result, it was observed that the buying intention of the dishes didn’t increase when they were highlighted with the organic attribute regarding its absence and the ecological conscience didn’t have any impact on the buying intention of dishes made with organic ingredients. From this result, the second study analyzed the influence of the organic attribute and pricing variation, considering processed and in natura food, in the context of two distinct supermarkets (one with and the other without credibility). 375 survey replies were collected and demonstrated that, despite the supermarket has no influence on buying intention, the constructs “price” and “ecological conscience” influenced, indeed, the buying intention of in natura and processed food. The consumers were willing to buy organic food, as long as the price difference, when compared to the traditional food, was small. At last, on the third experiment the manipulation of the organic attribute, in a context of real consumption, took place using tasting sessions of organic food with 230 respondents. It was observed that the construct “quality of the food” had the same influence on buying intention of organic food as on traditional food. In addition, the consumers didn’t have higher buying intention towards food tasted as organic. Regarding the limitations of this research, the non-probabilistic sample, very homogenous and consisting of mainly young people and residents of inland cities were evidenced. As a future research, the study of the influence of adding the organic stamp in packaging, as a mean to better understand how to add value to the product and how the consumers process this information, is suggested.